Blackwell guide to the philosophy of law and legal theory - Golding, Martin P. (Martin Philip), 1930-; Edmundson, William A. (William Atkins), 1948- (Malden, MA : Blackwell Pub., 2005)
A complete critical survey of the central themes and issues of the philosophy of law today. Focusing and advancing key arguments throughout, each essay incorporates essential background material serving to clarify the history and logic of the relevant topic.
Natural law theory / Mark C. Murphy -- Legal positivism / Brian H. Bix -- American legal realism / Brian Leiter -- Economic rationality in the analysis of legal rules and institutions / Lewis A. Kornhauser -- Critical legal theory / Mark V. Tushnet -- Four themes in feminist legal theory : difference, dominance, domesticity, and denial / Patricia Smith -- Criminal law theory / Douglas Husak -- Philosophy of tort law / Benjamin C. Zipursky -- Contract theory / Eric A. Posner -- The commons and the anticommons in the law and theory of property / Stephen R. Munzer -- Legal evidence / Alvin I. Goldman -- Legal and moral obligation / Matthew H. Kramer -- Theories of rights / Alon Harel -- A contractarian approach to punishment / Claire Finkelstein -- Responsibility / Martin P. Golding -- Legislation / Jeremy J. Waldron -- Constitutionalism / Larry A. Alexander -- Adjudication and legal reasoning / Richard Warner -- Privacy / William A. Edmundson -- Continental perspectives on natural law theory and legal positivism / Jes Bjarup -- Some contemporary trends in continental philosophy of law / Guy Haarscher -- Objectivity / Nicos Stavropoulos -- Can there be a theory of law? / Joseph Raz.
Includes bibliographical references and index.
Keywords: Law -- Philosophy; Droit -- Philosophie; Collection of essays